Uji Efektivitas Ekstrak Etanol Pakkat (Calamus caesius blume) Terhadap Kualitas Sperma Pada Tikus Wistar Jantan yang Diinduksi Aloksan - Wilbert Waldo Utomo (Faculty of Medicine, Universitas Andalas, 2021)
Objective: This study aimed to see the effectiveness of pakkat extract on the sperm quality of male wistar rats (Rattus novergicus) induced by alloxan. Methods: design of this research used an experimental design with a pre-test and post-test randomized control design, the samples used were 25 hyperglycemic rats divided into 5 groups: negative control (given NaCMC), positive control (metformin), treatment 1 (pakkat extract 125 mg/kgBW ), treatment 2 (250 mg/kgBW pakkat extract), treatment 3 (500 mg/kgBW pakkat extract) for 14 days. Results: The results showed that the extract of pakkat (Calamus caesius blume) with monitoring doses of 125 mg/kgBW and 250 mg/kgBW for 14 days continuously could reduce blood glucose levels of male wistar rats induced by alloxan with the results 216.60±128.74 and 160.20± 72.75 and also found to improve sperm quality of male wistar rats induced by alloxan. Conclusion: Pakkat (Calamus caesius blume) extract with doses of 125 mg/kgBW and 250 mg/kgBW can improve blood sugar levels and also sperm quality of male wistar rats induced by alloxan.